Substantive Justice in the Division of Marital Property in the Decision of the Mataram District Court Number 122/Pdt.G/2022/Pn.Mtr - Mirza Amelia; Hery Zarkasih; Siska Aprilia (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study is motivated by the increasing number of disputes over the division of marital property following divorce, which often lead to injustice, particularly for wives, due to an administrative evidentiary approach that tends to be formalistic. The main issue lies in the gap between procedural justice, which is legally oriented, and substantive justice, which should ensure the protection of the parties’ economic rights during marriage. This research aims to analyze the mechanism for the division of marital property based on the Civil Code and to examine its application in the Decision of the Mataram District Court Number 122/Pdt.G/2022/PN.Mtr. The method employed is normative legal research using statutory, conceptual, and case approaches. The results indicate that, normatively, the division of marital property is guided by Articles 119 and 128 of the Civil Code concerning community property. However, in practice, the panel of judges tends to emphasize the formal aspects of proof of ownership based on the date stated in property certificates. Such consideration overlooks the reality of joint financial contributions as well as the wife’s non-financial contributions within the household. These findings highlight the need for a paradigm shift among judges from a formal juridical approach toward a substantive justice orientation in order to ensure more equitable and fair legal protection in disputes over marital property.